Risk Stratification of Acute Pulmonary Embolism and Determining the Effect on Chronic Cardiopulmonary Complications: The REACH Study - Stevens, Hannah; Fang, Wendy; Clements, Warren; Bloom, Jason; McFadyen, James; Tran, Huyen (TH Open, 2020)
Introduction Patients with acute pulmonary embolism (PE) are at risk of developing chronic complications including the post-PE syndrome with reduced cardiopulmonary function and chronic thromboembolism pulmonary hypertension (CTEPH). Risk stratification at PE diagnosis is an important tool in predicting early mortality; however, its use in predicting chronic complications has not been evaluated.Objective This study investigates the effect of initial risk stratification of intermediate risk and standard risk PE on the rate of development of chronic complications including right ventricular (RV) dysfunction, residual perfusion defects, and CTEPH.Methods Cases of acute PE (n = 1,524) were identified using International Statistical Classification of Diseases and Related Health Problems, Tenth Revision, Australian Modification discharge diagnosis coding for PE. Evidence of RV dysfunction and systolic blood pressure < 90 mm Hg were used to risk stratify into high, intermediate and standard risk PE.Results There were 508 patients included in the analysis. Intermediate risk PE was associated with higher rates of persistent RV dysfunction as well as residual perfusion defects on repeat imaging. The overall rate of CTEPH was low (0.6%) and there was no difference between the intermediate risk and standard risk PE groups.Conclusion These findings demonstrate that acute intermediate risk PE is associated with higher rates of RV dysfunction on follow-up imaging than standard risk PE. However, the rate of CTEPH was similar between the two groups and overall the CTEPH rate was low among all patients with intermediate and standard risk PE.
Keywords: pulmonary embolism; risk stratification; venous thromboembolism; pulmonary hypertension; thrombosis